2019
DOI: 10.1002/hbm.24781
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of semantic cognition in Mandarin Chinese: A combined fMRI and TMS study

Abstract: While converging sources of evidence point to the possibility of a large‐scale distributed network for semantic cognition, a consensus regarding the underlying subregions and their specific function in this network has not been reached. In the current study, we combined functional magnetic resonance imaging (fMRI) and transcranial magnetic stimulation (TMS) methodology to investigate the neural basis of semantic cognition in Mandarin Chinese. In the fMRI experiment, strong activations were observed in left inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 84 publications
(137 reference statements)
0
9
0
Order By: Relevance
“…Besides, previous studies have reported many other brain areas implicated in semantic processing other than IFG. To be specific, activation of the left middle temporal gyrus (MTG) has been detected in a semantic judgment task (Zhang et al, 2019). The left MTG has been recognized as a store for semantic knowledge (Binder et al, 2009; Hickok & Poeppel, 2004), and it may also be involved in the retrieval of semantic information (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, previous studies have reported many other brain areas implicated in semantic processing other than IFG. To be specific, activation of the left middle temporal gyrus (MTG) has been detected in a semantic judgment task (Zhang et al, 2019). The left MTG has been recognized as a store for semantic knowledge (Binder et al, 2009; Hickok & Poeppel, 2004), and it may also be involved in the retrieval of semantic information (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To be specific, activation of the left middle temporal gyrus (MTG) has been detected in a semantic judgment task (Zhang et al, 2019). The left MTG has been recognized as a store for semantic knowledge (Binder et al, 2009; Hickok & Poeppel, 2004), and it may also be involved in the retrieval of semantic information (Zhang et al, 2019). Moreover, previous studies also found the left anterior temporal lobe to be a classical brain area implicated in semantic processing, like a “semantic hub” (Baron & Osherson, 2011; Westerlund & Pylkkänen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the temporal gyrus, which has often been observed with enhanced activation in reappraisal task (Goldin et al, 2008;Kanske et al, 2011;Dörfel et al, 2014), is usually considered as part of semantic system (Binder et al, 2009) and plays a role in both the storage and the strategic retrieval of semantic knowledge (Davey et al, 2016). Recent evidence on functional connectivity between IFG and MTG at both task (Zhang et al, 2019) and resting-state contexts (Kohn et al, 2014;Davey et al, 2016) indicates that the cooperation between IFG and MTG makes strategic access of semantic information possible. Similarly, the present study also revealed strong functional connectivity between IFG and temporal gyrus, alongside a positive correlation with medium habitual use of reappraisal, perhaps supporting the capacity to potentially engage and sustain semantic retrieval, in line with goal-driven control of subjective emotional feelings.…”
Section: Discussionmentioning
confidence: 99%
“…All participants underwent fMRI scanning in a 3.0‐T GE DISCOVERY MR750 scanner (General Electric Medical Systems, Milwaukee, WI) at the UESTC laboratory. Functional MR images were acquired with a gradient echo planar imaging (EPI) sequence, with the following scanning parameters, as in our previous study (Zhang et al, 2019): TR = 2000 ms, TE = 30 ms, flip angle = 90°, matrix size = 64 × 64, voxel size = 3.75 × 3.75 × 3 mm 3 , 43 slices. After a 6.5‐min resting‐state fMRI scan, we acquired high‐resolution whole‐brain volume T1‐weighted images obliquely with a 3D spoiled gradient echo pulse sequence (TR = 5.932 ms, TE = 1.956 ms, flip angle = 9°, matrix size = 256 × 256, FOV = 25.6 × 25.6 cm 2 , and slice thickness = 1 mm) to control for any anatomic abnormalities and to increase normalization accuracy during preprocessing.…”
Section: Methodsmentioning
confidence: 99%
“…All participants underwent fMRI scanning in a 3.0-T GE DISCOVERY MR750 scanner (General Electric Medical Systems, Milwaukee, WI) at the UESTC laboratory. Functional MR images were acquired with a gradient echo planar imaging (EPI) sequence, with the following scanning parameters, as in our previous study (Zhang et al, 2019): space (3 × 3 × 3 mm 3 ), and spatial smoothing with an 8-mm Gaussian kernel (full-width at half-maximum). Imaging in all participants met the standards of total vector motion <1.5 mm and rotation <1.5 .…”
Section: Fmri Data Acquisition and Preprocessingmentioning
confidence: 99%